A rising thunder - Weber, David, 1952- (Weber, David, 1952- Honor Harrington., 2012)
"After a brutal attack on the Manticoran home system, Honor Harrington has rooted out a plan designed to enslave the entire human species. Behind that plans lies the shadowy organization known as the Mesan Alignment. Task #1 for Honor is to shut down and secure the wormhole network that is the source of the Star Kingdom's wealth and power--but also its greatest vulnerability. Yet this is an act that the ancient and corrupt Earth-based Solarian League inevitably takes as a declaration of war. Once again Honor Harrington is thrust into a desperate battle that she must win if she is to survive to take the fight to the real enemy of galactic freedom"--